(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Ayurveda is an eternal branch considered as the science of life. Its prime motto is maintaining the health of healthy individual first and then curing the disease, which promotes a disease free, healthy life span. Ayurveda is an abundant ocean full of knowledge consisting of eight superior branches. Amongst them Shalya Tantra is the prime branch rich in surgical concept. History reveals that the period of Acharya Sushrut was the golden era of surgery where various surgical procedures were performed. More over in regards of anorectal and perineal surgery, Acharya has expounded much, with an approach of emphasise both surgical and Para surgical measures. Bhagandara can be screened in ancient Ayurvedic texts and varying systematic, scientific detailed descriptions are found. It is the common ano-rectal disease prevalent in the population worldwide. Because of its tedious nature of healing Bhagandara is considered difficult to be cured also it is found to be one amongst the Ashta Mahagada, where Acharya has explained the limitation of the treatment by considering it as Duschikitsya Vyadhi. Hence this article has emphasized on the available discretion on various types of Bhagandara and its management.